2015
DOI: 10.15587/2312-8372.2015.47700
|View full text |Cite
|
Sign up to set email alerts
|

Researching of heat transfer in the surface layer of the meat products at bilateral frying under the action of electric current

Abstract: Технологии пищевой, легкой и химической промышленносТи 47 Technology audiT and producTion reserves -№ 4/4(24), 2015,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the works [7][8][9] theoretical aspects of intensification of the process of meat products bilateral frying under the effect of physical and electrophysical methods were considered. The mechanism of heat conduction from frying surfaces to a product at the bilateral frying of meat is considered and theoretically grounded in the works [10,11]. At the same time the calculation of the coefficient of heat conduction through steam layers was offered.…”
Section: Food Science and Technologymentioning
confidence: 99%
“…In the works [7][8][9] theoretical aspects of intensification of the process of meat products bilateral frying under the effect of physical and electrophysical methods were considered. The mechanism of heat conduction from frying surfaces to a product at the bilateral frying of meat is considered and theoretically grounded in the works [10,11]. At the same time the calculation of the coefficient of heat conduction through steam layers was offered.…”
Section: Food Science and Technologymentioning
confidence: 99%
“…Study [13] analytically proves the possibility to intensify double-sided meat frying under the effect of the above-mentioned methods. The mechanism of heat transfer to each capillary meniscus through the vapor layer is considered and theoretically justified in [14,15], and the coefficient of heat transfer k through the vapor layers is proposed to be determined by the following formula:…”
Section: Heat Transfer Coefficient During Double-sided Meat Frying V mentioning
confidence: 99%
“…This need arises from the fact that studies [14,15] of liquid evaporation in the meniscus revealed an inaccuracy in determining the evaporation surface. Studies [14,15] note that the logarithmic mean surface of the meniscus during evaporation can be calculated as follows: …”
Section: Research Findings On the Effect Of Lmtd On The Heat Transfermentioning
confidence: 99%